2015
DOI: 10.1002/j.2334-5837.2015.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating an A3 Architecture Overview; a Case Study in SubSea Systems

Abstract: The subsea oil and gas domain suffers from complex and partially incomplete information flows. As consequence, most employees in the involved organizations lack overview of the systems and operations. Using conceptual modeling and A3 architecture overviews, we have reconstructed the overview for the workover system and its operation. The result triggers interest from the suppliers in the oil and gas domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 9 publications
3
25
0
Order By: Relevance
“…All feedback related to the models or the pictures, no participants commented on the "text sheet". The value of using models close that is close to the mental model of the system have been described in previous research on A3AOs in the subsea industry (Wee & Muller, 2015).…”
Section: Real Time Feedback During A3ao Creationsupporting
confidence: 68%
See 2 more Smart Citations
“…All feedback related to the models or the pictures, no participants commented on the "text sheet". The value of using models close that is close to the mental model of the system have been described in previous research on A3AOs in the subsea industry (Wee & Muller, 2015).…”
Section: Real Time Feedback During A3ao Creationsupporting
confidence: 68%
“…Findings showed that the method is well suited to enhance communication between engineering teams. Based on earlier SE research (Broches, 2010), (Løndal & Falk, 2017), (Wee & Muller, 2015) we wanted to address the subject of implicit knowledge sharing by using A3AOs.…”
Section: Knowledge Sharing In Development Projectsmentioning
confidence: 99%
See 1 more Smart Citation
“…According Sols (2014) the consequences of poor defective formulation of requirements in early phase of the life cycle will be evident as the project proceeds and that they can be dramatic. The work for (Tranøy & Muller, 2012) and (Muller, Wee, & Moberg, 2015) supports that this is a problem in the subsea industry. Due to the nature of the project life span of a subsea development, it expected that the stakeholder needs and requirements are changing from the study phase to the tender and execution phases.…”
Section: Identification Of Stakeholders and Concept Of Operationmentioning
confidence: 65%
“…When using A3AOs, Borches (2010) and Van de Laar & Punter (2010) suggested using multiple levels of abstraction in the A3 model. Muller, Wee & Moberg (2015) also found that creators of A3s tended to realize that they need multiple levels of abstractions.…”
Section: Literature Reviewmentioning
confidence: 97%